Deregulation of the Akt Pathway in Human Cancer - Tokunaga, Eriko; Oki, Eiji; Egashira, Akinori; Sadanaga, Noriaki; Morita, Masaru; Kakeji, Yoshihiro; Maehara, Yoshihiko (Current Cancer Drug Targets, 2008)
Akt (protein kinase B) is a serine/threonine kinase which is a central regulator of widely divergent cellular processes including proliferation, differentiation, migration, survival and metabolism. Akt is activated by a variety of stimuli, through growth factor receptors, in phosphatidylinositol 3-kinase (PI3K)-dependent manner. Akt is also negatively regulated by the tumor suppressor phosphatase and tensin homolog deleted on chromosome 10 (PTEN). A disruption of normal Akt/PKB/PTEN signaling frequently occurs in many human cancers, which plays an important role in cancer development, progression and therapeutic resistance. Numerous studies have revealed the blockage of Akt signaling to result in apoptosis and growth inhibition of tumor cells. Therefore, this signaling pathway, including both upstream and downstream of Akt, has recently attracted considerable attention as a new target for effective cancer therapeutic strategies. In fact, many inhibitors of Akt pathway have been identified and clinical studies of some agents are ongoing. In this review, we describe Akt signaling pathway components and its cellular functions as well as the alterations in human cancers and the therapeutic approaches for targeting the Akt pathway in cancer.
Keywords: receptor protein tyrosine kinase